Mapping of Acute Respiratory Infection (ARI) Vulnerability in Toddlers Based on Physical Condition of Houses in Palu City, Indonesia - Pitriani Pitriani; Annisa Melania; Vadia Almaratul M; Kiki Sanjaya; Vidyanto Vidyanto; Hasanah (Media Publikasi Cendekia Indonesia, 2022)
Acute Respiratory Infection (ARI) is one of the causes of high morbidity and mortality, especially in toddlers. The study purpose was to determine the susceptibility of ARI among children under five in these locations by considering the physical condition of houses (ventilation, density of occupancy, types of floors and walls). This research uses an ecological study with a Geographic Information System (GIS) approach. The research population in Talise health centre was 622 toddlers (sample 86) and Singgani health center was 1,167 toddlers (sample 93), samples were taken by Proportional Stratified Random Sampling based on the number of cases in each urban village in the study area. The results showed both of Talise and Singgani health centers the physical aspect of the houses was not associated with the incidence of ARI in children under five. Ventilation area with ρ-values 0.77 and 1.00, density with ρ-values 0.77 and 1.00, floor types with ρ-values 0.33 and 0.37, and wall types with ρ-values 0.75 and 1.00. Based on the results of the mapping at the two locations, it was found that the most vulnerable locations to ARI in infants with the highest number of vulnerable from all aspects of the physical condition of the house including ventilation area, occupancy density, type of floor, and type of wall were in the working area of the Singgani Health Center